KOMUNIKASI LINTAS BUDAYA ANTARA PEDAGANG LOKAL DENGAN WISATAWAN ASING DI PANTAI SANUR - Made Arya Astina; Ketut Muliadiasa (Institut Pariwisata dan Bisnis Internasional, 2017)
It is interesting to do research about the interaction between the local seller and the foreigners. The sellers who generally have Balinese cultural and basic educational background, every day to communicate with the tourists who have a language and a different culture. Based on the back ground of the problem, this research can be indicated into:Â (1) How is the pattern of cross-cultural communication with foreign tourists with local traders at Sanur Beach? (2) What are the factors which are supporting and threat the local traders in communicating with foreign tourists on the beaches of Sanur?. This research was conducted in the area of Sanur beach, which are in Semawang, Sindu, and Padang Galak. This research is used purposive sampling based on certain informants criteria. The type of this research is a descriptive study using a qualitative approach. In this study, presented the concept of patterns of communication, cross-cultural adaptation process, interpersonal communication, behavior in communication, the concept of cross-cultural communication. The conclusion of this research as follows: Model of cross-cultural communications of local traders with the foreign tourists that traders use communication with non-verbal language such as waving, handshakes, smiles and eye contact. Local traders also used verbal language by using short English sentences without paying attention to the pattern of correct English. Some things can be a cross-cultural communications support between trader and foreign tourists are cultural vendorsâ€™ factors at Sanur beach who have an open character and friendly towards strangers. Another factor is the economic factor needs traders are trying to communicate with the settlers. While considered as a limiting factor is the lack of mastering a good English As well as the lack of understanding of the excellent service to the tourists.